Islamic Spiritual Education Through Visiting Patient App For Brain Tumor Patients - Wahyudin Wahyudin; Lantip Rujito; Alfi Muntafiah; Arfi Nurul Hidayah (Comprehensive Health Care, 2023)
Brain tumor patients may experience stress due to changes in their health, daily life, and intense head pain. Prolonged stress can worsen their condition and cause depression, hindering their treatment process. The study consisted of two groups, each with 15 participants. However, after some withdrawals, the final sample for Group 1 was 11, and Group 2 was 7. The stress, anxiety, and depression levels were measured using the DASS 42 questionnaire before and after the intervention, which involved providing the Visiting Patient app to Group 1 and not to Group 2. Data was collected every 4 to 5 days using the same questionnaire. The app, which contains Islamic educational content on the positive aspects of illness and rewards, increases the patient's spiritual knowledge and helps them adopt a positive attitude towards their condition, reducing stress, anxiety, and depression. It allow them to cooperate better with their treatment process.